TRANSFER PRICING SCHEME AS A TOOL FOR TAX AVOIDANCE AT MULTINATIONAL COMPANY IN INDONESIA - Peace Kanne Natalia; Ria Nelly Sari; Vince Ratnawati (PEKBIS, 2019)
The focus of this study are the practices of tax avoidance through transfer pricingschemes undertaken by multinational companies in Indonesia. In addition, this studyalso explore the preventing program taken by government of Indonesia in order toreduce tax avoidance practices. This is a qualitative study with in depth interviewsas a technique to collect the data. The key informants for this study are governmentofficial from Directorate General of Taxes (DGT), academicians and tax consultant.The results revealed that multinational company in Indonesia practice some taxavoidance scheme such as overstates costs, understates sales, intangible property,contractual agreements, and also uses the services of tax consultants to utilizeexisting loopholes. This study suggest that the government of Indonesia should bemore proactive in assuring that exchanging information with other countries is runeffectively, so that the purpose of OECD which is to minimize or even to prevent taxavoidance practices will occur. Beside that government of Indonesia also need tostrengthen the regulation related with transfer pricing practices. In accordance withthe suggestion above, government of Indonesia also need to practice the goodhuman resources management system, so that every tax government official isposition in a proper job. With the good human resources management system it willcause the practice of reward and punishment. The exchange of information has asignificant role especially for tax payers database. The database can be expandaccess to data and information about tax payers.